The Influence of Leadership Style, Work Facilities, and Salary on Employee Motivation - Nicky, Nicky; Hendratmoko, Hendratmoko (Ridwan Institute, 2025)
This study aims to analyze the influence of leadership style, technology-based work facilities, and salary systems on employee work motivation at PT. Elektrindo Sarana Abadi. In a volatile economy, companies must maintain the stability and sustainability of their operations. The workforce is a key element in achieving organizational goals, and an adaptive leadership style, adequate work facilities, and a fair compensation system greatly influence work motivation. This study uses a quantitative approach with the Multiple Linear Regression Analysis method using SmartPLS ver.4. The research sample consisted of 100 respondents who were employees of PT. Elektrindo Sarana Abadi. The study results show that digital leadership style, work facilities, and salary significantly influence employee work motivation. Simultaneously, these three variables also have a significant effect on work motivation. These findings underscore the importance of developing leadership training programs to improve managerial skills and employee motivation, periodic audits and improvements to work facilities, and adjustments to salary structures and incentive systems so employees feel financially valued. In addition, implementing a regular performance evaluation system and the use of feedback from employees for continuous improvement are highly recommended. The study concludes that flexible and adaptive leadership approaches, adequate work facility support, and a fair compensation system are crucial in increasing employee motivation in an increasingly technology-connected work environment. Further research is suggested to explore other factors influencing work motivation and expand the research object to different industry contexts.